Prescripción inadecuada en pacientes polimedicados mayores de 64 años en atención primaria() - Filomena Paci, Josefina (Aten Primaria, 2015)
OBJECTIVE: To describe inappropriate prescribing (IP) in the polymedicated population over 64 years-old in primary care using the STOPP/START criteria. DESIGN: The study design was descriptive, cross-sectional and multicenter. LOCATION: Four urban primary care centers in Barcelona. Participants Patients over 64 years-old with more than 5 prescribed drugs for at least 6 months (n = 467). Main measurements Major health problems, chronically prescribed drugs, and percentage of IP using the STOPP/START criteria were studied. Percentage of IP considered as the percentage of patients with at least one STOPP or START non-compliance criterion was calculated with a 95% CI. Chi-square was used for statistical analysis. RESULTS: The mean age was 77.3 (± 7.0 SD) with a mean of 8.9 (± 2.8 SD) prescribed drugs. IP was higher the greater the number of drugs prescribed (p < 0,01). 326 patients (76.4% [95% CI: 72.2 to 80.6]) had at least one IP, according to STOPP/START criteria. STOPP IP affected 51.4% of the patients and START IP 53.6%. The most frequent causes of IP were antiplatelet agents, for both over-prescribing (10.2%) and omission (17.9%). Prolonged use of benzodiazepines (6.6%) and duplications (6.4%) followed in prevalence. CONCLUSIONS: IP in polymedicated patients in primary care was very high. IP was similar for drugs that should be withdrawn or started. The most common causes of IP were antiplatelet agents, benzodiazepines and drug duplication.